Effect of rare earth elements substitution in La site for LaMnO3 Manganites - Wong, Jen Kuen; Lim, Kean Pah; Shaari, Abdul Halim; Chen, Soo Kien; Ng, Siau Wei; Gan, Albert Han Ming (Universiti Putra Malaysia Press, 2012)
With a view to understanding the effect of rare earth element (Ce, Pr, Nd, Sm and Gd) substitution for the La site in LaMnO3 (LMO), the samples were prepared via solid-state reaction. Structure investigation by X-ray diffraction (XRD) showed that structure transformation from trigonal (LMO) to orthorhombic (PMO, NMO, SMO and GMO) occurred when smaller trivalent rare earth element was replaced. The MnO6octahedra were tilted and elongated or compressed, corresponding to the ionic radii of the rare earth inserted. Meanwhile, microstructure study using scanning electron microscopy (SEM) illustrated that La substitution by another rare earth element caused a reduction in grain size. This might due to the changes in enthalpy of fusion by other rare earth ions, where higher enthalpy of fusion favours formation of smaller grain size. However, CeMnO3 did not form under this preparation condition. The magnetic properties studied from the hysteresis plot taken at room temperature indicated that the substitution of La with other magnetic trivalent rare earth ions strongly weakened the magnetic strength of the system.